shRNA-mediated gene silencing of HDAC11 empowers CAR-T cells against prostate cancer - Zhang, Hongmei; Yao, Jie; Ajmal, Iqra; Farooq, Muhammad Asad; Jiang, Wenzheng (Frontiers in Immunology, 2024)
Epigenetic mechanisms are involved in several cellular functions, and their role in the immune system is of prime importance. Histone deacetylases (HDACs) are an important set of enzymes that regulate and catalyze the deacetylation process. HDACs have been proven beneficial targets for improving the efficacy of immunotherapies. HDAC11 is an enzyme involved in the negative regulation of T cell functions. Here, we investigated the potential of HDAC11 downregulation using RNA interference in CAR-T cells to improve immunotherapeutic outcomes against prostate cancer. We designed and tested four distinct short hairpin RNA (shRNA) sequences targeting HDAC11 to identify the most effective one for subsequent analyses. HDAC11-deficient CAR-T cells (shD-NKG2D-CAR-T) displayed better cytotoxicity than wild-type CAR-T cells against prostate cancer cell lines. This effect was attributed to enhanced activation, degranulation, and cytokine release ability of shD-NKG2D-CAR-T when co-cultured with prostate cancer cell lines.Our findings reveal that HDAC11 interference significantly enhances CAR-T cell proliferation, diminishes exhaustion markers PD-1 and TIM3, and promotes the formation of T central memory TCM populations. Further exploration into the underlying molecular mechanisms reveals increased expression of transcription factor Eomes, providing insight into the regulation of CAR-T cell differentiation. Finally, the shD-NKG2D-CAR-T cells provided efficient tumor control leading to improved survival of tumor-bearing mice in vivo as compared to their wild-type counterparts. The current study highlights the potential of HDAC11 downregulation in improving CAR-T cell therapy. The study will pave the way for further investigations focused on understanding and exploiting epigenetic mechanisms for immunotherapeutic outcomes.